Violent student protests in higher education institutions: exploring the formations of violence and the socio-economic costs of violent protests - Khiba, Teboho Aubrey (University of the Free State, 2023)
This study investigated the academic and financial impacts of violent student protests on students and the University. Within this background, this study adopted an interpretive paradigm to understand the lived experiences of students who have participated in violent student protests. In addition, the study looks at how staff members are affected by violent protests in the discharge of their duties. The study comes against the background of an upsurge in violent student protests with adverse consequences for both students and institutions of higher education in South Africa. The study adopted a qualitative design, and the sample included students from various political parties, student organisations, and staff personnel from different departments at the University of Free State (UFS). The sample of the study was made up of 15 participants. These included nine students and six staff. Of the total participants, two were females while fourteen were males. Participants were recruited using purposive and snowball sampling strategies. Data for this study were collected through online and face-to-face interviews using an interview schedule. In analysing data for this study, inductive thematic analysis was used. The theoretical framework used in this study included the theory of interpersonal violence, the Fanonian perspective on violence, and the emergent norm theory. The study found that lack of response, leadership, diverse agendas, individual selection, retaliation, as well as the presence of police and private security emerged as essential factors contributing to violence or violent acts during protests. Moreover, the study found that restricted access to campus resources, loss of study time, and suspensions of some student activists were notable consequences encountered after protests. In addition, the study found that transport and legal fees were among some of the financial costs incurred by students due to violent protests. Furthermore, the study found that services offered by the University, such as administration and academic services, come to a stop when protests occur on campus. This impedes staff members’ duties as protests become a priority where substantial money is spent on acquiring extra security and replacing or fixing any damaged property due to student protests.
Dissertation(M.Soc.Sc.(Sociology))--University of the Free State, 2023
Keywords: Costs; Court order; Policies; Protests; Security; Violence